HEALTH CHECK TO IMPROVE QUALITY OF LIFE OF ELDERLY KUMBASARI MARKET TRADERS - Paramurthi, I.A. Pascha; Astiti Suadnyana, Ida Ayu; Yoga Krismantara, I Ketut Arya (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Community service carried out by Physiotherapy Study Program Lecturers at the Faculty of Health Sciences, University of Bali International was carried out at Kumbasari Market which also involved students in the Physiotherapy Study Program. The purpose of this activity is for elderly traders in Kumbasari Market to know general health conditions such as blood pressure, pulse, diet, sleep quality, physical activity, cognitive and quality of life, and have the awareness to be able to maintain health to create an optimal quality of life. The importance of maintaining quality of life can affect daily activities so that the elderly in old age can be more productive. The method used in this activity is the method of examination and providing education to participants. The existence of this activity is expected so that the elderly can maintain and improve general health conditions such as blood pressure, pulse, diet, sleep quality, physical activity, and cognition so that the quality of life of the elderly can be maintained.